Nutritional knowledge of patients diagnosed with endocrinopathies - Grot, Martina; Szajdewig, Magdalena; Grajek, Mateusz; Białek-Dratwa, Agnieszka; Sobczyk, Karolina (Journal of Education, Health and Sport, 2022)
Background: Thyroid diseases including Hashimoto's chronic lymphocytic thyroiditis represent an increasing epidemiological problem of the 21st century. Thyroid disease is estimated to affect approximately 7.0-9.0 per cent of the population up to the age of 60 years, and as much as 10.0-12.0 per cent after the age of 60 years. Hashimoto's disease is much more common among women of childbearing age, but it is also increasingly common among children and adolescents. The number of reported cases of autoimmune thyroiditis is steadily increasing. The aim of this study was to assess the nutritional knowledge of female patients with Hashimoto's disease in selected closed online support groups for patients with thyroid disease. Materials and methods: A self-administered online survey questionnaire was used to conduct the study. Results: 321 women were enrolled in the study. The largest group of respondents, aged between 20 and 40 years, lived in cities with more than 100 000 inhabitants and had a university education. Hypothyroidism along with Hashimoto's disease was declared by the largest number of respondents. The respondents' main source of nutritional knowledge was the media; the level of knowledge was assessed as insufficient. Conclusions: There is a need to increase nutritional education among patients in order to reduce the incidence of disease complications, the development of other comorbidities and will allow for health-promoting effects during the pharmacotherapy process.